Socioeconomic Roles in Cesarean Section Delivery in the Philippines: A Secondary Analysis of the 2022 National Demographic and Health Survey - Yunitawati, Diah; Laksono, Agung Dwi; Wulandari, Ratna Dwi; Latifah, Leny; Effendi, Diyan Ermawan; Hidayat, Taufiq; Nugraheni, Wahyu Pudji; Batangan, Dennis B. (Nurse Media Journal of Nursing, 2025)
Background: Cesarean section (CS) delivery should only be performed with medical indications. It is important to analyze the socioeconomic role in CS and determine how to address socioeconomic-related factors in optimizing CS coverage in the Philippines using the latest national data.Purpose: This study analyzed the socioeconomic roles in CS delivery in the Philippines.Methods: This study used secondary data from the 2022 Philippines National Demographic and Health Survey (NDHS). The cross-sectional study included 4,452 women aged 15–49 who had given birth within the previous three years. Seven control factors were examined: employment, antenatal care (ANC), age, education, marital status, residence, and parity. The mode of delivery was considered the outcome variable, while socioeconomic status was the exposure variable. Binary logistic regression was used for the final data analysis.Results: Cesarean section was performed in 18.45% of deliveries in the Philippines. Analysis of socioeconomic status showed that women in the “poorer” group were 1.758 times more likely than the poorest to undergo CS (AOR 1.758; 95% CI 1.757–1.758). Women in the middle-income group were 2.164 times more likely than the poorest to have a CS (AOR 2.164; 95% CI 2.163–2.165). Those in the richer group were 2.718 times more likely (AOR 2.718; 95% CI 2.717–2.719), and the richest were 4.787 times more likely to deliver by CS compared to the poorest (AOR 4.787; 95% CI 4.785–4.789).Conclusion: Socioeconomic disparities are strongly associated with CS delivery in the Philippines. The wealthier the mother, the more likely she is to have a CS. Efforts should focus on reducing unnecessary CS in the rich and richest groups. Optimizing ANC education should include addressing psychological needs, promoting positive values, and providing a sense of security and comfort in normal childbirth. At the same time, equitable access to CS should be ensured for the poorest groups through education and insurance coverage.